How to compare relative age effect in different sports? A new methodological approach—example of youth olympic games - Cular, D.; Babic, M.; Katovic, D.; Beslija, T.; Kezic, A. (Sports, 2024)
This research aimed to propose a new methodological approach for analyzing relative age effect (RAE) in different sports or samples named "Relative age effect overall scale" (RAEOS). The sample consisted of 1455 male and female young athletes who competed in four different sports (basketball, n = 159; handball, n = 215; swimming, n = 981; taekwondo, n = 100) at the Youth Olympic Games (YOG) in Buenos Aires in 2018. To construct the new model, the sample was classified into four unified quartiles of a specific range depending on the sport (swimming: 48-month range, taekwondo: 24-month range, and basketball and handball: 36-month range). Expected and observed frequencies for each sport, the winners/all athletes, and differences between team and individual sports were analyzed using a non-parametric Chi-square test. The obtained results confirm the existence of the RAE in all four analyzed sports (p > 0.01) in a sample of all participants and the sample of gold medalists. Differences between team and individual sports in the analyzed sample have also been found. The proposed methodological approach (RAEOS) is a simple and applicable tool that provides opportunities for comparison and analysis of different sports and competition formats, as well as improvement of the sports talent system in the context of RAE issues. It is suggested to the sports decision-makers to improve the YOG qualification and competition system to enable fairer competition and reduce the influence of RAE on the performance and development of young athletes.